New discoveries in child psychotherapy : findings from qualitative research - Rustin, Margaret; Rustin, Michael (London : Routledge, 2019)
"New Discoveries in Child Psychotherapy presents eleven new contributions to child psychoanalytic research, most of them based on the experience of the clinical consulting room. Each chapter is the work of an experienced child psychotherapist or child analyst, vivid in their description of the children and families they encountered. Their understanding of the "inner worlds" of patients and the clinical consulting room is clearly evidenced in their analysis of clinical presentations. The chapters are the result of the psychoanalytic clinical and observational practices of their authors, allied to their use of rigorous qualitative research methods, in particular Grounded Theory and interpretative phenomenological analysis (IPA). They describe developments of child psychoanalytic knowledge in several fields, including autism, psychotherapy with severely deprived children, and the study of early infancy. They demonstrate advances in child psychoanalytic theories and methods and the development of new forms of clinical service provision. Contested issues in psychoanalytic research are thoroughly evaluated, showing how it can be made more accountable and rigorous through the adaptation of established qualitative research methods to the study of unconscious mental phenomena. New Discoveries in Child Psychotherapy will be an essential text in the field of child psychoanalysis and will be highly useful in psychotherapy and psychoanalysis training courses and for psychoanalytic researchers, as well as for practitioners."--
Keywords: Psychotherapy -- methods; Child; Qualitative Research